Study on Industrial Wastewater Pollution Monitoring Technology Based on NB-IoT Wireless Communication Technology - Liu, Tong; Qin, Feng (International journal of grid and high performance computing, 2025)
This study establishes a coupling model between Narrowband Internet of Things (NB-IoT) wireless communication technology and the degree of industrial water pollution, evaluating the influence of NB-IoT on industrial water pollution monitoring precision. Results show that NB-IoT wireless communication technology significantly increases the precision of industrial water pollution monitoring to 0.96 compared to traditional wire communication technology at 0.65. Additionally, the precision of industrial water pollution monitoring also changes with the economic scale, with an economic scale of 800,000,000,000 making the precision reach 0.89. Overall, this study suggests that wireless communication technology based on NB-IoT is more conducive to ecological environment protection through improved industrial water pollution monitoring.